HARTA BERSAMA SUAMI ISTRI DITINJAU DARI HUKUM ISLAM DAN HUKUM ADAT - Muhammad Ridwan; Arbanur Rasyid; Maulana Arafat Lubis (Institut agama islam negeri Padangsidimpuan, 2021)
Shared assets in the family have been regulated in Islamic law and customary law. This aims to apply justice in the household, between husband and wife. The existence of joint property due to partnership or partnership in general matters. Meanwhile, joint property in household life is due to the existence of a legal marriage bond between a man and a woman, as long as in the marriage bond both collect the property, both individually and together. However, if there is a dispute in the distribution of joint assets, Islamic law offers a solution of As-shulhu (peace) and kinship deliberation to find a mutually beneficial and satisfying way out, on the contrary in the legislation in force in Indonesia, joint property is divided into two, namely between husbands and wife after divorce.